2015
DOI: 10.1097/scs.0000000000001556
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multilevel Surgical Treatment on Mean Platelet Volume in Patients With Obstructive Sleep Apnea Syndrome

Abstract: One-stage multilevel surgery targeting the obstruction at the retropalatal and tongue-base levels was found to be effective in decreasing AHI and MPV. Mean platelet volume may be a new index to indicate the success of OSAS surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another study by Kurt et al reported a meaningful correlation between PDW and AHI (17). Moreover in some studies, it was proposed that treatment with continuous positive airway pressure (CPAP) devices and surgical intervention significantly reduce MPV and PDW values in patients with severe OSA (10)(11)(12)24). On contrary, almost similar number of study reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 81%
“…Another study by Kurt et al reported a meaningful correlation between PDW and AHI (17). Moreover in some studies, it was proposed that treatment with continuous positive airway pressure (CPAP) devices and surgical intervention significantly reduce MPV and PDW values in patients with severe OSA (10)(11)(12)24). On contrary, almost similar number of study reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 81%
“…Increased platelet activity could contribute to an increased atherothrombotic risk in patients with OSA. CPAP reported to cause a significant decrease in the MPV and PDW values in patients with OSA,9, 10 and this suggested that early diagnosis and CPAP therapy may confer some cardioprotective effects through the reduction of platelet activation.…”
Section: Discussionmentioning
confidence: 94%
“…The result of the study showed that OSA is independently associated with subsequent major adverse cardiac and cerebrovascular events, claiming the need for additional studies to evaluate of therapeutic approaches to mitigate OSA‐associated risk 5. Interestingly, some clinical studies showed that severe OSA significantly increases the level of MPV and platelet reactivity, and CPAP therapy significantly reversed this effect 7, 9. Rahangdale et al have previously reported in a small cohort ADP‐induced platelet aggregation was markedly increased in OSA patients 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilevel surgery targeting the retropalatal and tongue-base was effective in reducing mean platelet volume and apnea hypopnea index. Mean platelet volume is known to be predictors of cardiovascular diseases, hypertension, and stroke [115]. Surgery is effective at improving overnight polysomnography in obese children [116].…”
Section: Invasive Treatmentmentioning
confidence: 99%